Analysis of pressure distribution in cylindrical tube fluid flow using a fiber Bragg grating - Annisa Ratna Pertiwi; Saktioto Saktioto; Bambang Widiyatmoko; Dwi Hanto (Indonesian Physics Communication, 2024)
Fibre optic sensors have garnered considerable attention from scientists, leading to the extensive use of optical fibres as sensors for monitoring strain and temperature. The increasing adoption of fibre Bragg gratings (FBG) can be attributed to their enhanced sensitivity and rapid transmission speed. The objective of this study is to examine the pressure distribution of FBGs within a cylindrical tube while subjected to vibrations from a loudspeaker and the presence of hot water vapour. The given options were of two scenarios, first scenario had a tube without water vapour and a heart sound, while the second scenario included a tube with water vapour and a heart sound. In this experiment, we strategically placed the FBG at 20 different points along the cylindrical tube to accurately detect strain values at each position. The outcomes derived from these two scenarios illustrate that temperature and air vapour pressure exert an influence on the occurrence of sound, with the highest level of tension found when hot water vapour and heart sounds are present.